Hypersonic Vehicles Applications, Recent Advances, and Perspectives - Pezzella, Giuseppe; Viviani, Antonio (IntechOpen, 2022)
Some sixty years after the experimental flights of the North American X-15 hypersonic rocket-powered aircraft, sustained hypervelocity travel is still the next frontier in high-speed transportation. Today, there is much excitement and interest regarding hypersonic vehicles. In fact, many aerospace agencies, large industries, and several start-ups are involved in design activities and experimental campaigns both in wind tunnels and in-flight with full-scale experimental flying test beds and prototypes to make hypersonic travel almost as easy and convenient as airliner travel. Achieving this goal will radically revolutionize the future of civil transportation. This book contains valuable contributions that focus on various design issues related to hypersonic aircraft.